General Characteristics of the Circumstances Excluding Criminal Liability under the Criminal Law of Muslim Countries Practicing the Anglo-Saxon Law - E. Rizayeva , Dana; Abdul Karim Manna, Ammar (International Journal of Psychosocial Rehabilitation, 2020)
Islamic criminal law does not contain any institutions of the General Part; therefore, there is no general list of circumstances that exclude the criminality of the act done. The main research objective of the presented study was to form an idea on the basis of foreign legal literature of the role of existing circumstances that exclude liability under the criminal law of Muslim countries professing the Anglo-Saxon legal system, as well as to analyze the current actual criminal law; the study employed, in particular, comparative legal, dialectical, structural-functional, and formal-logical methods. A distinctive feature of Islamic law is the priority of the religious norms of Islam, which regulate all spheres of Muslims’ lives. The question of the role of circumstances excluding criminal responsibility under the criminal law of Muslim countries practicing Anglo-Saxon law is considered by current Islamic law in the prospect of accurate qualification of the criminal act committed, as well as in order to establish the very legitimacy of such an act. According to the analysis conducted, the following list of circumstances excluding liability under the criminal law of Muslim countries can be identified: not reaching the age of responsibility, state of insanity, delusion, committing a crime under duress, justifiable defense, extreme necessity, and repentance.